Re: Submitting list of manpower - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the submission of the list of manpower and health guidelines for them to prevent coronavirus infection at BRACU new campus project site.